Програма фізики спіну для детектора sPHENIX нового покоління на колайдері RHIC - Nakagawa, I.; for the sPHENIX Collaboration (Publishing house "Academperiodika", 2024)
The sPHENIX experiment is a new experiment and its new detector of Relativistic Heavy Ion Collider (RHIC) in the Brookhaven National Laboratory. It is an upgrade of the PHENIX experiment. The sPHENIX is to complete the scientific mission of RHIC in the study of QGP and the spin structure of the proton. The sPHENIX detector provides precision vertexing, tracking and electromagnetic and hadronic calorimetry in the central pseudorapidity region |η| ≤ 1.1, with full azimuth coverage, at the full RHIC collision rate, delivering unprecedented data sets for hard probe tomography measurement at RHIC. The sPHENIX was commissioned using Au + Au collision in 2023, and took physics data with transversely polarized proton + proton collisions at the center-of-mass energy of √S = 200 GeV in 2024. The status of detector commissioning and achieved physics targets of the proton spin program using the sPHENIX detector will be discussed.